2020
DOI: 10.1016/j.ejmech.2020.112721
|View full text |Cite
|
Sign up to set email alerts
|

Selective targeting of the αC and DFG-out pocket in p38 MAPK

Abstract: The p38 MAPK cascade is a key signaling pathway linked to a multitude of physiological functions and of central importance in inflammatory and autoimmune diseases. Although studied extensively, little is known about how conformation-specific inhibitors alter signaling outcomes. Here, we have explored the highly dynamic back pocket of p38 MAPK with allosteric urea fragments. However, screening against known off-targets showed that these fragments maintained the selectivity issues of their parent compound BIRB-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…To further show that FANCC regulated microglial pyroptosis via a p38/NLRP3 dependent pathway, the p38 inhibitor BIRB 796 and an NLRP3 inhibitor glyburide were employed to induce p38/NLRP3 signaling blockade, respectively [ 25 , 26 ]. WB showed that OE-FANCC decreased p-p38 and NLRP3 protein levels, which were further reduced after treatment with BIRB 796 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To further show that FANCC regulated microglial pyroptosis via a p38/NLRP3 dependent pathway, the p38 inhibitor BIRB 796 and an NLRP3 inhibitor glyburide were employed to induce p38/NLRP3 signaling blockade, respectively [ 25 , 26 ]. WB showed that OE-FANCC decreased p-p38 and NLRP3 protein levels, which were further reduced after treatment with BIRB 796 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Replacement of the terminal primary amide with the N -ethyl- N -methyl tertiary amide led to a selective type-II inhibitor of p38α despite weaker potency (IC 50 = 14 nM). It was tested against a 468-kinase panel at 1 µM concentration and inhibited only thirteen kinases including p38α and p38β (98.5% and 96.6% inhibition, respectively) [ 71 ].…”
Section: Pyrazole-based P38α/mapk14 Kinase Inhibitorsmentioning
confidence: 99%
“…In addition, 137 induced an antiinflammatory response by blocking TNF-α release in whole blood and displayed a high metabolic stability. [45] Compound 137 was tested against a panel of 468 kinases and kinase mutants. It showed favorable selectivity, with only seven detected off-targets: DDR1/2, ZAK, ABL1, STK11, MAP3 K4 and EPHA1.…”
Section: P38 Mapk Inhibitors In Vitro Studiesmentioning
confidence: 99%
“…Compound 137 inhibited p38α and p38β in cellulo with low nanomolar potencies, whereas only micromolar potencies were determined for the off-targets. [45] Kaieda et al (2018) realized an extensive SAR analysis of imidazo [1,2-b]pyridazine derivatives, discovering the compound 10a, which have a type I mode of inhibition and strongly inhibited p38 (IC 50 : 4,4 nM) and the production of TNF-α in human THP-1 cells. The in vitro structural analysis of the metabolites of compound 10a resulted in the discovery of pyridine N-oxide 15a (IC 50 : 5.4 nM) which exhibited a dramatically improved metabolic stability in human liver microsomes.…”
Section: P38 Mapk Inhibitors In Vitro Studiesmentioning
confidence: 99%